COMPARISON OF EFFICACY OF INTRALESIONAL TRIAMCINOLONE ACETONIDE VERSUS COMBINATION OF INTRALESIONAL TRIAMCINOLONE WITH 5-FLUOROURACIL IN TREATMENT OF KELOIDS: A RANDOMIZED CONTROLLED TRIAL - Naseem, Sadia; Paracha, Mohammad Majid; Sagheer, Farah; Abdul Qayyum; Noor, Sahibzada Mahmood (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the efficacy of conventionally used Triamcinolone Acetonide (TCA) in the treatment of keloids versus its combination with 5 fluorouracil (FU). Methodology: In this randomized control trial, 60 patients were included 30 in each group. A combination of triamcinolone and 5-FU was given to Group-A while Group B was administered intralesional triamcinolone in combination with 5 FU. The Efficacy was deemed as positive if post-treatment was a more than 70 % reduction in Patient and Observer Scar Assessment Scale (POSAS) from baseline. Results: Mean age of the patients was 33.6±8.8 and 32.1±8.8 years in group-A and B, respectively. There were 12 males (40%) in group-A and 14 (46.7%) in group B. Females were 18 (60%) in group-A while 16 (53.3%) were in group B. Most of the patients were having Fitzpatrick skin type 4 in both groups. Efficacy was found to be 28 (93.3%) in group-A and 19 (63.3%) in group B (p=0.005). Stratification for age, gender, and Fitzpatrick skin type was also carried out. Conclusion: This study concluded that the intralesional TCA was effective in 63.3% and a combination of intralesional 5-FU and TCA was effective in 93.3% of cases of keloids. This difference in efficacy is statistically significant (p=0.005).